Poultry Production, Management and Bio-Security Measures - Sharma, Banshi (Journal of Agriculture and Environment, 2010)
Poultry farming is an emerging industry in Nepal. Hygienic poultry production can pave way to better income and sustainable development. Poultry health management is important due to emergence of highly pathogenic diseases like Highly Pathogenic Avian Influenza (HPAI) in different parts of the world. Bio-security measures become vital for better performance and quality of poultry production in competitive world. The latest technological innovations may help adoption of bio-security measures and environment friendly practices in poultry production system. Bio-security policy can be formulated with the participation of stakeholders. It would give new dimensions towards poultry farming in different clusters in Nepal. Moreover, participatory response of poultry entrepreneurs to the programs prioritizing poultry disease investigation, eradication and safe guarding poultry industry would be valuable. There must be research tie up with different institute regarding production, processing and marketing of poultry products. Key words: Bio-security; Environment; Nepal; Poultry health management; Poultry Performance; Quality-control The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 120-125 Uploaded date: 16 September, 2010